STUDY OF BEIDOU SATELLITE CONTRIBUTION ON THE DETERMINATION OF STATIC, RTK, AND RT-PPP POSITIONG USING HEMISPHERE S321 RECEIVER - Rumengan - Nim: 15113084, Errandyno
GNSS which is currently growing has become one of the main choices in positioning. BDS, which is a GNSS system owned by China, is a new addition to the GNSS line that has operated globally. The Hemisphere S321 receiver is a GNSS signal receiver that is capable of receiving signals from the BDS satellite and is able to perform positioning by static methods, RTK, and RT-PPP. Therefore, this research was conducted which aims to see how much the BDS satellite contribution is in positioning with static, RTK, and RT-PPP. The research was done using three methods which are; radial static, RTK, and RT-PPP. To be more precise, the data from the static method that will be used as the deduction value to see the accuracy of the RTK and RT-PPP methods of the Hemisphere S321 tool. The three methods are carried out in two sessions where the first session uses data from all satellites (including BDS), and the second session uses no data from the BDS satellite. BDS satellites contribute to precision improvement of observational data on the determination of static positions, RTK, and RTPPP. BDS contribution is not very visible in the accuracy of the determination of static positions, RTK, and RT-PPP. The data quality provided by the Hemisphere S321 receiver is classified as good data, seen from the values of Dilution of Precision (DOP), Satellite Signal Visibility, Sky Plot, Signal to Noise Ratio (SNR), and Multipath.